Risk factors for carotid artery distensibility in middle-aged and elderly hemodialysis patients - Ren, Hong-qi (Second Affiliated Hospital of Zhejiang University School of Medicine, 2011)
BACKGROUND: Carotid intima media thickness (CIMT) and stiffness are taken as useful surrogate markers of atherosclerosis. In China, the number of elderly patients undergoing hemodialysis has increased year by year, with the increase of dialysis-related cardiovascular events. This study was undertaken to examine carotid stiffness in elderly hemodialysis patients by the ultrasound techniques in order to find out the possible risk factors. METHODS: From January 2006 to February 2010, a total of 87 patients (41 males and 46 females) treated with routine hemodialysis at the 97th Hospital of People’s Liberation Army were enrolled in this study. The distensibility coefficient (DC) of the carotid artery was detected by Doppler ultrasonic diagnosis apparatus (Philips HBI5000, frequency 12 MHz) for evaluation of arterial stiffness. Serum albumin, total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL), triglyceride (TG), glucose, creatinine, calcium, phosphorus, and intact parathyroid hormone (iPTH) were examined with standard methods. The liner correlation and multiple stepwise regression analysis were used to find correlations between them. RESULTS: In this study, the systolic blood pressure was 153.33±25.98 mmHg, DBP 84.22± 10.39 mmHg, TC 4.39±1.05 mmol/L, TG 1.36±0.72 mmol/L, LDL 2.47±0.77 mmol/L, Cr 889.82± 207.38 Mmol/L, Glu 5.36±1.87 mmol/L, Ca I 2.00±2.19±0.21 mmol/L, and DC 13.39±5.32×10(−3)/kPa. DC was associated with age (r=−0.459, P<0.001), SBP (r=−0.527, P<0.001), and serum calcium (r=−0.273, P=0.011). The multiple stepwise regression analysis showed that SBP, age, increased serum calcium level, and diabetes were independent risk factors for decreasing DC. CONCLUSION: Systolic blood pressure, age, increased serum calcium level and diabetes in elderly hemodialysis patients are independent risk factors for increased carotid arterial stiffness.